Emphysema is associated with increased inflammation in lungs of atherosclerosis-prone mice by cigarette smoke: implications in comorbidities of COPD - Yao Hongwei; Hwang Jae-woong; Sundar Isaac K; Arunachalam Gnanapragasam; Rahman Irfan (BMC, 2010)
Abstract Background Chronic obstructive pulmonary disease is associated with numerous vascular effects including endothelial dysfunction, arterial stiffness and atherogenesis. It is also known that a decline in lung function is associated with increased cardiovascular comorbidity in smokers. The mechanism of this cardiopulmonary dual risk by cigarette smoke (CS) is not known. We studied the molecular mechanisms involved in development of emphysema in atherosclerosis-prone apolipoprotein E-deficient (ApoE-/-) mice in response to CS exposure. Methods Adult male and female wild-type (WT) mice of genetic background C57BL/6J and ApoE-/- mice were exposed to CS, and lung inflammatory responses, oxidative stress (lipid peroxidation products), mechanical properties as well as airspace enlargement were assessed. Results and Discussion The lungs of ApoE-/- mice showed augmented inflammatory response and increased oxidative stress with development of distal airspace enlargement which was accompanied with decline in lung function. Interestingly, the levels and activities of matrix metalloproteinases (MMP-9 and MMP-12) were increased, whereas the level of eNOS was decreased in lungs of CS-exposed ApoE-/- mice as compared to air-exposed ApoE-/- mice or CS-exposed WT mice. Conclusion These findings suggest that CS causes premature emphysema and a decline of lung function in mice susceptible to cardiovascular abnormalities via abnormal lung inflammation, increased oxidative stress and alterations in levels of MMPs and eNOS.